Competition with Identity Driven Entry: A Principal Multi-Agent Model on the Success of Mergers and Acquisitions - Burchhardt, Sebastian (Springer, 2015)
Sebastian Burchhardt develops a game theory model that analyzes the possible behavioral patterns of employees during M&A processes and the impact of such patterns on the success of the transaction itself. The result is the development of a principal-multi-agent model that allows for endogenous contest entry driven by identity. In addition, the model proposes guidance for practical M&A management.